Checklist of Fish Species Richness of Jai Prakash Narayan Bird Sanctuary, Suraha Lake, Ballia, U.P., India - Srivastava, P.K.; Srivastava, S.K. (Our Nature, 2010)
Present paper deals with the fish species richness of the Suraha Lake. The study was made during August 2002-July 2004. In the course of investigation at three sampling spots Mairitar, Surajpura and Basantpur, 54 fish species were recorded under 7 orders and 20 families. Twentyone species of Cypriniformes, 12 species of Siluriformes, 3 species of Symbrachiformes, 13 species of Perciformes, 1 species of Tetradontiformes, 3 species of Clupeiformes and 1 species of Beloniformes have been recorded. Key words: Jai Prakash Narayan Bird Sanctuary, Suraha lake, fish species richness DOI: 10.3126/on.v7i1.2573 Our Nature (2009) 7:207-211